Relationship between organizational culture and performance: literature review of the mediating and moderating effects - ER RHAIMINI , Hilal Maryama; CHARAF , Karim (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The relationship between organizational culture (OC) and organizational performance (OP) provides fertile ground and several opportunities for research. For this reason, and since several decades, many researchers from a variety of disciplines have shown a growing interest on this link. However, the lack of consensus on the definitions of the relevant concepts, combined with the multiplication of measurement models and the mixed but also inconclusive character of the findings from the conducted empirical studies, prevent the assertion of a direct, positive and strong link between OC and OP. According to several theorists, there are mechanisms through which OC influences OP. Some even assume that formalizing a third variable will be necessary to establish this link. However, no study has yet identified the precise nature of these mediating and moderating variables mentioned in the literature. Therefore, this research work aims to fill this gap and provide researchers and managers with a documentary search from several databases to clearly identify these mechanisms and variables. In this context, proposals will be presented as well as a conceptual model to be tested empirically in a later study. Following this, we will conclude the present study by highlighting its implications and outlining potential directions for future research.